Natural Killer and T Cell Infiltration in Canine Osteosarcoma: Clinical Implications and Translational Relevance - Razmara, Aryana M.; Judge, Sean J.; Gingrich, Alicia A.; Cruz, Sylvia M.; Culp, William T. N.; Kent, Michael S.; Rebhun, Robert B.; Canter, Robert J. (Frontiers in Veterinary Science, 2021)
Metastatic osteosarcoma has a bleak prognosis in both humans and dogs, and there have been minimal therapeutic advances in recent decades to improve outcomes. Naturally occurring osteosarcoma in dogs is shown to be a highly suitable model for human osteosarcoma, and limited data suggest the similarities between species extend into immune responses to cancer. Studies show that immune infiltrates in canine osteosarcoma resemble those of human osteosarcoma, and the analysis of tumor immune constituents as predictors of therapeutic response is a promising direction for future research. Additionally, clinical studies in dogs have piloted the use of NK transfer to treat osteosarcoma and can serve as valuable precursors to clinical trials in humans. Cytotoxic lymphocytes in dogs and humans with osteosarcoma have increased activation and exhaustion markers within tumors compared with blood. Accordingly, NK and T cells have complex interactions among cancer cells and other immune cells, which can lead to changes in pathways that work both for and against the tumor. Studies focused on NK and T cell interactions within the tumor microenvironment can open the door to targeted therapies, such as checkpoint inhibitors. Specifically, PD-1/PD-L1 checkpoint expression is conserved across tumors in both species, but further characterization of PD-L1 in canine osteosarcoma is needed to assess its prognostic significance compared with humans. Ultimately, a comparative understanding of T and NK cells in the osteosarcoma tumor microenvironment in both dogs and humans can be a platform for translational studies that improve outcomes in both dogs and humans with this frequently aggressive disease.